Взаимодействие упругих волн с цилиндрической полостью в условиях плоской деформации - Назаренко, А. М.; Панченко, Б. Е.; Ложкин, А. М. (НТУ "ХПИ", 2005)
The problem of elastic waves diffraction on a cylindrical space is dealt with. The problem is brought to solving singular equations, which are calculated numerically. Dependence of the space boundary voltage on dynamic, mechanical and geometrical characteristics are presented
Keywords: дифракция плоских гармонических волн; вектор перемещений; волновое поле; амплитудные значения